Catalytic Decomposition of Methane to Hydrogen over Al2O3 Supported Mono- and Bimetallic Catalysts - Gaukhar E. Ergazieva; Nursaya Makayeva; Zhanna Shaimerden; Sergiy O. Soloviev; Мoldir Telbayeva; Еrzhan Akkazin; Fariza Ahmetova (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
This article discusses the decomposition of methane in the temperature range 550–800 °C on low-percentage   monometallic (Ni/g-Al2O3, Co/g-Al2O3) and bimetallic (Ni-Co/g-Al2O3) catalysts. It is shown that the bimetallic catalyst is more active in the decomposition of methane to hydrogen than monometallic ones. At a reaction temperature of 600 °C, the highest methane conversion is 81%, and the highest hydrogen yield of 51% is formed on Ni-Co/g-Al2O3. A complex of physicochemical methods (Scanning Electron Microscope (SEM), X-ray Diffraction (XRD), Temperature Programmed Reduction (TPR-H2), etc.) established that the addition of cobalt oxide to the composition of Ni/g-Al2O3 leads to the formation of surface bimetallic Ni-Co alloys, while the dispersion of particles increases and the reducibility of the catalyst is facilitated, which provides an increase in the concentration of metal particles - active centers, which can be the reason for an increase in the catalytic properties of a bimetallic catalyst in comparison with monometallic ones. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License  (https://creativecommons.org/licenses/by-sa/4.0).